State Policy of Supply Chain Management in the Shere of Physical Culture and Sport in the Russian Federation - Chyvatkin P.P.; Rokotyanskaya V.V.; Yushin I.V.; Usanov A.Yu.; Yakh'yaeva M.U. (International Journal of Supply Chain Management, 2019)
The article examines the theoretical foundations of State governance in physical fitness and sports, the legislation in the field of physical culture and sports, the structure of sports administration in the Russian Federation based on the supply chain management. The medium and long-term strategies for the development of physical culture and sports have been analyzed. The current state policy in the development of physical culture and sports at the federal level has been estimated. The methods of improving state policy in the field of physical culture and sports, including at the legislative level, have been developed.